Spindle cell lipoma mimicking pleomorphic adenoma: A diagnostic challenge on cytology. Issue 4 (23rd November 2018) - Kaur, Manveen; Chatterjee, Debajyoti; Kundu, Reetu; Punia, Rajpal S.; Saini, Vaibhav
Abstract : Spindle cell lipoma (SCL) is a benign neoplasm of mature adipose tissue mostly located in the neck, back, and shoulder region. It is composed of a variable admixture of adipocytes, benign spindle cells, and collagen fibres. While the histopathologic features of SCL are quite characteristic and well described, a cytologic diagnosis of SCL might be challenging. We present a case of a 36‐year‐old female with a swelling in the left preauricular region since last 6 mo. On fine needle aspiration, a diagnosis of lipomatous pleomorphic adenoma (PA) was rendered because of the presence of benign spindle‐shaped cells, adipocytes, and abundant myxoid material. However, on histopathologic examination, the diagnosis was SCL which was confirmed by immunohistochemistry. Preauricular region is a rare site of occurrence of SCL. An acquaintance with its varied cytomorphologic features and a knowledge of its unusual sites of occurrence is essential to prevent its misdiagnosis as other myxoid benign and malignant spindle cell lesions.